The Effect of Tourist Experience on Satisfaction and Revisit Intention in Forest Tourism - Santosa Utomo Humam; Widjanarko Hendro; Suratna Suratna; Rahmawati Keny; Hasan Muqaddas Fadli (SHS Web of Conferences)
This study aims to examine and analyze the influence of tourist experiences visiting forest tourism on satisfaction and revisit intention. This study was conducted in the forest area of the slopes of Mount Lawu, Central Java, Indonesia. The respondents of this study were undergraduate or diploma level students who had visited the destination in the last two years. This study involved 100 respondents who were selected accidentally. Data is processed using WarpPLS. The findings of this study indicate that the tourist experience has a significant effect on satisfaction, tourist experience has a significant effect on revisit intention, and satisfaction has a significant effect on revisit intention.